(untitled) (Research, Society and Development, 2022)
Dental treatments have been adopted in order to improve the quality of life of edentulous patients. In this aspect, implants are widely used to replace missing teeth. Implant-supported rehabilitation shave been shown to be safe, with high success rates. Such indices are linked to osseointegration, direct, stable and distant union between living bone structure and implant surface. However, factors must be considered for the consolidation of this biological event. This integrative literature review, with a qualitative analysis of works published since 2002, which deal with the theme “early loss of dental implants”, aim to clarify factors as sociated with the success/ failure of osseointegration. The analyzed bibliography was extracted from the Scientific Electronic Library Online (Scielo), Google Scholar and Pubmed databases, using the keywords “Health Teaching”, “Osseointegration”, “Dental Implant” and “Bone-Implant Interface” in English and portuguese, with the addition of the Boole an operator “and” between them. Articles that fit the theme, with methodological clarity, availability of the full text, in English and Portuguese, were included. The material provided clarification on osseointegration, in addition to clarifying clinical doubts, constituting guidance material for clinical dental practices, pointing out that the success of osseointegration is strongly linked to the clinical conditions of the patient.